Enhancement of Biomass Production in Colony-Forming Green Algae, Botryosphaerella sudetica, Under Mixotrophic Cultivation - Yun, Hyun-Sik; Kim, Young-Saeng; Yoon, Ho-Sung (Frontiers in Genetics, 2021)
In this study, we characterized the potential of colony-forming green algae, Botryosphaerella sudetica KNUA107, isolated from Ulleung Island, South Korea, as a bioresource and analyzed the effects of mixotrophic cultivation on its bioresource production efficiency. Internal transcribed spacer (ITS) (ITS1, 5.8S, and ITS2), ribulose bisphosphate carboxylase large subunit (rbcL), and elongation factor Tu (tufa) regions were used for molecular identification and phylogenetic analysis. B. sudetica KNUA107 had a strong relationship with the green algae of Botryococcus and Botryosphaerella genera, which are colony-forming species, and was also associated with members of the Neochloris genus. To improve biomass productivity, we tested mixotrophic cultivation conditions using several organic carbon sources. Glucose supplementation stimulated B. sudetica KNUA107 growth and reduced the time needed to reach the stationary phase. In addition, the colony size was 1.5–2.0 times larger with glucose than in photoautotrophic cultures, and settleability improved in proportion to colony size. The total lipid content and biomass productivity were also higher in cultures supplemented with glucose. Among the lipid components, saturated fatty acids and monounsaturated fatty acids had the highest proportion. Our study suggests that B. sudetica KNUA107, which has enhanced efficiency in biomass production and lipid components under mixotrophic cultivation, has high potential as a bioresource.